Seasonal and Spatial Dynamics of Chlorophyll-a Concentrations in Marine Protected FMA 714 in Relation to Yellowfin Tuna (Thunnus albacares) Catches - Tadjuddah, Muslim; Sambah, Abu Bakar; Sadarun, Baru; Wianti, Nur Isiyana (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Indonesia's Ministry of Marine Affairs and Fisheries designated Fisheries Management Area 714 (FMA 714) as a tuna conservation area.  Research has been conducted on the potential fishing grounds, distribution, and abundance of YFT in FMA 714. Still, a study that analyzes catch productivity and YFT coordinates with YFT conservation area distance has never been done. The objectives of this study are to analyze the seasonal and spatial dynamics of Chl-a concentrations in FMA 714 using temporal spatial analysis with SeaDAS 9.0.1, analyze fishing productivity by season using CPUE analysis, and determine the distance of the fishing ground from the conservation area using point distance geoprocessing analysis in GIS. The data used are logbook data from YFT caught with pole and line in the form of fishing coordinates, several catches, and seasonal Chl-a concentrations from 2019-2021, and catch per unit effort to analyze fishing productivity. The results showed that the highest average Chl-a concentration in FMA 714 was dominated by the eastern monsoon, transition period II, transition period I, and the western monsoon period. Transition period II had the highest CPUE, 19.50 fish/fishing set, and the lowest CPUE was found in the eastern monsoon, 0.36 fish/fish set. The fishing area has a moderate chlorophyll-a concentration but tends to yield a high CPUE and there is a tendency for high CPUE to be relatively far from the tuna conservation area.